(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examined the role of agricultural cooperatives in addressing food insecurity among farming households in Etsako West Local Government Area of Edo State, Nigeria. Specifically, the study assessed the contribution of agricultural cooperatives to household food security, identified the services provided by cooperative societies, and examined the challenges affecting their effectiveness. A descriptive survey research design was adopted for the study. Primary data were collected through the administration of structured questionnaires to 150 members of selected agricultural cooperative societies using a multistage sampling technique. Data were analysed using descriptive statistics, including frequencies, percentages, means, and standard deviations, while multiple linear regression analysis was employed to determine the effect of agricultural cooperative activities on household food security at a 5% level of significance. The findings revealed that agricultural cooperatives significantly improved members’ access to agricultural credit, farm inputs, extension services, collective marketing, and training programmes, thereby enhancing agricultural productivity and household food security. The regression results further indicated that agricultural cooperative activities had a positive and statistically significant effect on household food security. However, inadequate capital, poor government support, high production costs, weak rural infrastructure, and limited access to finance were identified as major constraints affecting the effectiveness of agricultural cooperatives. The study concluded that agricultural cooperatives remain effective instruments for improving food security and rural livelihoods in Etsako West Local Government Area. The study therefore recommends increased government support, improved access to agricultural finance, strengthened extension services, and enhanced institutional capacity to improve the performance of agricultural cooperative societies and promote sustainable food security.